2019
DOI: 10.1080/14786419.2019.1655411
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided fractionation and identification of antidiabetic compounds from the rind of Punica Granatum Var. nana

Abstract: This study aimed to evaluate the antidiabetic potential of the rind of Punica granatum var. nana. Acute oral toxicity test revealed the safety profile of its ethanolic extract. The extract was administered at 200 mg/kg b.wt to streptozotocin-induced diabetic rats. Serum diagnostic markers of diabetes (insulin, glucose and glycated hemoglobin), inflammatory mediators (tumor necrosis factor-α, interleukin-6, and nitric oxide), and oxidative stress (total antioxidant capacity and reduced glutathione and malondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…In 2017, around 425 million adults in the age group of (20-79 years) reported to affect by diabetes and estimated to grow to 629 million by 2045 (Saeedi et al 2019). Nowadays, combined therapy with several oral hypoglycemic agents is used to manage diabetes, but therapies possess numerous side effects (Choudhary et al 2020;El Deeb et al 2019;Ullah Jan et al 2018). However, effective and safe treatment in curing diabetes is yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, around 425 million adults in the age group of (20-79 years) reported to affect by diabetes and estimated to grow to 629 million by 2045 (Saeedi et al 2019). Nowadays, combined therapy with several oral hypoglycemic agents is used to manage diabetes, but therapies possess numerous side effects (Choudhary et al 2020;El Deeb et al 2019;Ullah Jan et al 2018). However, effective and safe treatment in curing diabetes is yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…has also been found in P. granatum L., and many of the mechanisms of action reported by the authors are related with the high concentration of bioactive compounds of secondary metabolism of the fruit, specially ellagic acid, gallic acid, punicic acid and flavonoids as quercetin and kaempferol [ 45 , 77 , 82 , 85 , 87 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Finally, the consumption of P. granatum L., including the peel and edible parts, as well as its extracts, are considered safe in vitro and in vivo [ 103 , 104 , 105 , 106 , 107 , 108 , 109 ], and these results agree with the non-cytotoxicity results of P. protopunica Balf., however, more studies in P. protopunica Balf. are required to conclude that.…”
Section: Discussionsupporting
confidence: 69%
“…It has shown that a food grade pomegranate fruit extract, administered orally, in an acute toxicity study, had a LD 50 of more than 5000 mg/kg in Wistar rats and Swiss albino mice and in the sub chronic study all animals survived and no changes in clinical parameters (physical and behavioral) were observed [92]. In other study, the result of the oral acute toxicity (OECD 2001), revealed no signs of toxicity in a peel extract at fixed sole dose of 2000 mg/kg for 14 days [93]. In addition, the butanolic fraction of methanolic extract of pomegranate peel was evaluated in an acute toxicity test, finding that it, was safe at a dose above 500 mg/kg [94].…”
Section: Toxicitymentioning
confidence: 87%